Development of PD3 and PD3-B for PDEδ inhibition to modulate KRAS activity. (31st December 2022) - Lee, Jungeun; Lee, Ho Jin; Lee, Yeongcheol; Lim, Bumhee; Gam, Jongsik; Oh, Dong-Chan; Lee, Jeeyeon
Abstract: Despite extensive efforts over 40 years, few effective KRAS inhibitors have been developed to date, mainly due to the undruggable features of KRAS proteins. In addition to the direct approach to KRAS via covalent inhibition, modulation of the prenyl-binding protein PDEδ that binds with farnesylated KRAS has emerged as an alternative strategy to abrogate KRAS activity. For the verification of new therapeutic strategies, chemical probes with the dual functions of visualisation and pharmacological inhibition against oncogenic proteins are enormously valuable to understand cellular events related to cancer. Here, we report indolizino[3, 2-c]quinoline (IQ)-based fluorescent probes (PD3 and PD3-B ) for PDEδ inhibition. By using the unique fluorescent characteristics of the IQ scaffold, a fluorescence polarisation (FP)-based binding assay identified PD3 as the most effective PDEδ probe among the tested PD analogues, with a low K d value of 0.491 µM and long retention time in the binding site of PDEδ. In particular, a FP-based competition assay using deltarasin verified that PD3 occupies the farnesylation binding site of PDEδ, excluding the possibility that the FP signals resulted from non-specific hydrophobic interactions between the ligand and protein in the assay. We also designed and synthesised PD3-B (5 ), an affinity-based probe (ABP) from the PD3 structure, which enabled us to pull down PDEδ from bacterial lysates containing a large number of intrinsic bacterial proteins. Finally, KRAS relocalization was verified in PANC-1 cells by treatment with PD3, suggesting its potential as an effective probe to target PDEδ.